1999
DOI: 10.1046/j.1460-2695.1999.00224.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue behaviour of a box‐welded joint under biaxial cyclic loads

Abstract: Multiaxial fatigue behaviour of box‐welded (wrap‐around) joints in a JIS SM400B steel (12‐mm‐thick plate) was examined using a biaxial fatigue test facility. For the specimen, two stiffeners were attached to a main plate by a CO2 semi‐automatic welding procedure. Residual stress measurements and finite element (FE) analyses were also performed. Fatigue tests were performed under both uniaxial and biaxial (mainly out‐of‐phase) cyclic loads, and both results were compared and examined. It was found that fatigue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 7 publications
1
23
0
Order By: Relevance
“…In Ref. [9], the reference stress range Δ σ 5 in the x ‐direction 5 mm away from the box‐weld toe was mainly used for correlating the uniaxial and biaxial fatigue data. This parameter has been shown to be an effective parameter when considering the quantitative effects of loads in the y ‐direction and for estimating the biaxial fatigue lives from uniaxial test data.…”
Section: Results Of Fatigue Tests and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In Ref. [9], the reference stress range Δ σ 5 in the x ‐direction 5 mm away from the box‐weld toe was mainly used for correlating the uniaxial and biaxial fatigue data. This parameter has been shown to be an effective parameter when considering the quantitative effects of loads in the y ‐direction and for estimating the biaxial fatigue lives from uniaxial test data.…”
Section: Results Of Fatigue Tests and Discussionmentioning
confidence: 99%
“…However, only a few reports have been issued in which the fatigue of welded joints under orthogonal biaxial pulsating tensile loads was experimentally examined 8 . The present authors previously performed biaxial fatigue tests under pulsating tensile loads with a phase difference of π ; these being on box‐welded (wrap‐around) cruciform joint specimens which showed that biaxial fatigue lives were well correlated using a reference stress range, Δ σ 5 9 …”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations